Eficacia de la Timpanoplastía tipo III con interposición de cartílago en Otitis Media Crónica Simple - Zapata Erauste, Erick Alberto (2019)
Suppurated chronic otitis media is still one of the most common diseases in developing countries among low socioeconomic strata population. In addition, suppurated chronic otitis media is a potentially serious disease because of its complications, caused by the progressive erosion of the temporal bone, thus increasing the risk of damage to the facial nerve, labyrinth and dura. It is also a common cause of hearing impairment and disability. The purpose of this work is to demonstrate the effectiveness of Tympanoplasty III using cartilage grafts, which empirically has shown good results with a low cost, so we want to statistically evaluate the auditory improvement after surgery.